Association of Air Pollution and Mental Disorders in the Greater Metropolitan Area of Costa Rica, 2016-2019 - Jiménez Seas, Mónica; Chamizo García, Horacio Alejandro; Villegas Gonzáles, Nicole; Sibaja Brenes, José Pablo (Población y Salud en Mesoamérica, 2025)
Introduction: Various studies have identified exposure to nitrogen dioxide (NO2), particulate matter (PM10) and other pollutants as a risk factor for the incidence of mental disorders. However, these associations have not been previously explored in Costa Rica. Methods: An ecological-geographic study was designed at the district level in the Greater Metropolitan Area (GAM) of Costa Rica. Data on suicide events, suicide attempts, and depression were obtained from 154 districts of the GAM of Costa Rica; along with data on two pollutants: NO2 and PM10 for a period of four years (2016 to 2019). Data were correlated using a robust negative binomial regression model and a geographically weighted regression. Results: The association between pollutants and suicide was positive, but not significant, the same happened with the relationship between NO2 and suicide attempt. The model shows a negative but non-significant relationship between PM10 and suicide attempt, while an increase of one unit of NO2 (> 40μg/m3) was linked to a higher incidence rate of depression (percentage change: 9.50%, CI:5.00% to 14.00%). Conclusions: Higher levels of pollution were associated with an increase in the incidence rate of depression in the GAM districts of Costa Rica. The association between pollutants and suicide and suicide attempt and the independent variables cannot be affirmed or rejected. It is necessary to indicate other possible ways of configuring the relationship with more explanatory variables.